The role of Ag+, Ca2+, Pb2+ and Al3+ adions in the SERS turn-on effect of anionic analytes - Iancu, Stefania D.; Stefancu, Andrei; Moisoiu, Vlad; Leopold, Loredana F.; Leopold, Nicolae (Beilstein Journal of Nanotechnology, 2019)
In our recent studies we highlighted the role of adsorbed ions (adions) in turning on the surface-enhanced Raman scattering (SERS) effect in a specific mode for anionic and cationic analytes. In this work, we emphasize the role of Ag+, Ca2+, Pb2+ and Al3+ adions in the specific adsorption of anionic analytes such as the citrate capping agent and three organic acids. Our results suggest an adion-specific adsorption mechanism: the adsorption of anionic analytes is facilitated by positively charged adions such as Ag+, Ca2+, Pb2+ or Al3+, which provide adsorption sites specific for the anionic analytes. The turn-on of the SERS effect is explained in the context of the chemical mechanism of SERS. The adions form SERS-active sites on the silver surface enabling a charge transfer between the adsorbate and the silver surface. High-intensity SERS spectra of uric acid, salicylic acid and fumaric acid could be recorded at a concentration of 50 µM only after activation of the colloidal silver nanoparticles by Ca2+, Pb2+ or Al3+ (50 µM). The chemisorption of the three anionic species to the silver surface occurs competitively and is enhanced with the anions of higher affinities to the silver surface as indicated by the SERS spectra of corresponding mixed solutions.
Keywords: adion-specific adsorption model; cation bridging; Raman; surface enhanced Raman scattering (SERS)

(untitled) - Kneipp, K.; Kneipp, H.; Itzkan, I.; Dasari, R. R.; Feld, M. S. (Chem. Rev., 1999)

(untitled) - Kneipp, J.; Kneipp, H.; Kneipp, K. (Chem. Soc. Rev., 2008)

(untitled) - Wetzel, H.; Gerischer, H.; Pettinger, B. (Chem. Phys. Lett., 1981)

(untitled) - Billmann, J.; Kovacs, G.; Otto, A. (Surf. Sci., 1980)

(untitled) - Otto, A. (Surf. Sci., 1978)

(untitled) - Hildebrandt, P.; Stockburger, M. (J. Phys. Chem., 1984)

(untitled) - Otto, A.; Bruckbauer, A.; Chen, Y. X. (J. Mol. Struct., 2003)

(untitled) - Watanabe, T.; Kawanami, O.; Honda, K.; Pettinger, B. (Chem. Phys. Lett., 1983)

(untitled) - Muniz‐Miranda, M.; Sbrana, G. (J. Raman Spectrosc., 1996)

(untitled) - López-Tocón, I.; Valdivia, S.; Soto, J.; Otero, J. C.; Muniz-Miranda, F.; Menziani, M. C.; Muniz-Miranda, M. (Nanomaterials, 2019)

(untitled) - Zoppi, A.; Caporali, S.; Muniz-Miranda, F.; Pedone, A.; Muniz-Miranda, M. (ACS Appl. Nano Mater., 2019)

(untitled) - Doering, W. E.; Nie, S. (J. Phys. Chem. B, 2002)

(untitled) - Leopold, N.; Stefancu, A.; Herman, K.; Tódor, I. S.; Iancu, S. D.; Moisoiu, V.; Leopold, L. F. (Beilstein J. Nanotechnol., 2018)

(untitled) - Stefancu, A.; Iancu, S. D.; Moisoiu, V.; Leopold, N. (Rom. Rep. Phys., 2018)

(untitled) - Beltramo, G. L.; Shubina, T. E.; Mitchell, S. J.; Koper, M. T. M. (J. Electroanal. Chem., 2004)

(untitled) - Stewart, A.; Murray, S.; Bell, S. E. J. (Analyst, 2015)

(untitled) - Arenas, J. F.; Castro, J. L.; Otero, J. C.; Marcos, J. I. (J. Raman Spectrosc., 1995)

(untitled) - Li, Y.-S.; Cheng, J.; Wang, Y. (Spectrochim. Acta, Part A, 2000)

(untitled) - Bell, S. E. J.; Sirimuthu, N. M. S. (J. Phys. Chem. A, 2005)

(untitled) - Marsich, L.; Bonifacio, A.; Mandal, S.; Krol, S.; Beleites, C.; Sergo, V. (Langmuir, 2012)

(untitled) - Garrido, C.; Diaz-Fleming, G.; Campos-Vallette, M. M. (Spectrochim. Acta, Part A, 2016)

(untitled) - Castro, J. L.; Arenas, J. F.; López-Ramírez, M. R.; Peláez, D.; Otero, J. C. (J. Colloid Interface Sci., 2009)

(untitled) - Alvarez-Puebla, R. A.; Arceo, E.; Goulet, P. J. G.; Garrido, J. J.; Aroca, R. F. (J. Phys. Chem. B, 2005)

(untitled) - Bonifacio, A.; Dalla Marta, S.; Spizzo, R.; Cervo, S.; Steffan, A.; Colombatti, A.; Sergo, V. (Anal. Bioanal. Chem., 2014)

(untitled) - Leopold, N.; Lendl, B. (J. Phys. Chem. B, 2003)

(untitled) - Stefancu, A.; Moisoiu, V.; Couti, R.; Andras, I.; Rahota, R.; Crisan, D.; Pavel, I. E.; Socaciu, C.; Leopold, N.; Crisan, N. (Nanomedicine (London, U. K.), 2018)

(untitled) - Gallardo, O. A. D.; Moiraghi, R.; Macchione, M. A.; Godoy, J. A.; Pérez, M. A.; Coronado, E. A.; Macagno, V. A. (RSC Adv., 2012)

(untitled) - Linnert, T.; Mulvaney, P.; Henglein, A. (J. Phys. Chem., 1993)

(untitled) - Scanlon, M. D.; Peljo, P.; Méndez, M. A.; Smirnov, E.; Girault, H. H. (Chem. Sci., 2015)

(untitled) - Chaudhari, K.; Ahuja, T.; Murugesan, V.; Subramanian, V.; Ganayee, M. A.; Thundat, T.; Pradeep, T. (Nanoscale, 2019)

(untitled) - Feig, D. I.; Mazzali, M.; Kang, D.-H.; Nakagawa, T.; Price, K.; Kannelis, J.; Johnson, R. J. (J. Am. Soc. Nephrol., 2006)

(untitled) - Moisoiu, V.; Socaciu, A.; Stefancu, A.; Iancu, S. D.; Boros, I.; Alecsa, C. D.; Rachieriu, C.; Chiorean, A. R.; Eniu, D.; Leopold, N.; Socaciu, C.; Eniu, D. T. (Appl. Sci., 2019)

(untitled) - Baddiel, C. B.; Cavendish, C. D.; George, W. O. (J. Mol. Struct., 1970)

Infrared and Raman Spectroscopy (Second Edition - Larkin, P. J. (Chapter 6 - IR and Raman Spectra–Structure Correlations: Characteristic Group Frequencies, 2018)

(untitled) - Attard, G. A. (J. Electroanal. Chem., 2018)

(untitled) - Jaeger, H.; Sanders, J. V. (J. Res. Inst. Catal., Hokkaido Univ., 1968)

Encyclopedia of Interfacial Chemistry - Vattuone, L.; Savio, L.; Rocca, M. (Influence of Defects on Adsorption—Model Studies With Stepped Surfaces, 2018)

(untitled) - Lee, P. C.; Meisel, D. (J. Phys. Chem., 1982)